APLIKASI PERANGKAT LUNAK GENERATOR PAKET TCP/IP BERBASIS GRAPHICAL USER INTERFACE (GUI) DENGAN Qt - Utsalina, Dwi Safiroh; Kuncoro, Trias Mukti (DINAMIKA DOTCOM, 2011)
Analyzing computer networks is an activity usually conducted by people working in the world of information technology especially in the field of computer networks. Often, when analyzing a computer network, need to generate network traffic the computer that can be determined freely. Network traffic in the form of blocks of bytes of a well-defined structure, called packets. To do so can only be made possible with the tools that one of his form in the form of software that can build a packet (packet generator) to then be sent to the network. In building the computer network packets needed a programming library that handles the packaging details, his name libnet. Libnet latest version (libnet-1.1) has advantages over its predecessor is in accordance with the concept of a layer of TCP / IP.Â  With the latest version of libnet, methods build the same package with the concept of wrapping the layer of TCP / IP, the higher layer is wrapped by a lower layer. So that can be generated a packet generator software principles of computer networks that works with the concept of a layer of TCP / IP. And because the graphics-based, it can be possible to be made more flexible in handling packages. In addition, because using the frame-work of both Qt and libnet-free operating system platform, the development is not closed only on Linux-based operating system, but also other operating systems like Windows family of operating systems and Mac OS.Â Keywords: Generator, package, TCP/IP, libnet, Qt